EFFECTS OF MICROFINANCE SERVICES ON THE FINANCIAL PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES IN MOGADISHU, SOMALIA - MOHAMED, MOHAMUD AHMED; Mukhongo, Aaron L (IJRDO - Journal of Business Management, 2016)
In this study titled the effect of microfinance services on the financial performance of small and medium enterprises, a case study of microfinance institutions in Mogadishu, Somalia. Most of the small and medium enterprises in Somalia fail in their premature state, because of lack of insufficient capital, lack of risk awareness and the absence of financial literacy. The major objective of this study was to measure the relationship between these above variables, the independent and dependent respectively. The specific objectives for this study include ascertaining how financial sustainability affects financial performance in small and medium enterprises in Mogadishu. The findings about this study stated that financial sustainability, financial literacy and risk diversification have moderate positive relationship with financial performance of microfinance institutions in Mogadishu. The target population for this study consisted of four microfinance institutions Salam Somali Bank, Dahabshiil, Trust African bank and Kaah microfinance enterprise. Sample of 82 respondents was taken. The sample was chosen by using Slovene’s formula. Sampling technique for this study was non-random sampling particularly purposive sampling. Descriptive research design was employed. Structured questionnaire have been designed to facilitate the acquisition of relevant data which was used for analysis. Descriptive statistics which involves simple tables and illustrations was tactically applied in data presentations and analysis. Regression model was used to measure the kind of relationship that exists between the independent and the dependent variable. The results of the study showed that moderate positive relationship exists between financial sustainability, financial literacy, risk diversification and financial performance of microfinance institutions in Mogadishu, Somalia. The researcher would like to recommend for the microfinance institutions to expand their services to other parts of the country to distribute the opportunities that can be benefited by the poor citizens in entire the country